Research on Reinforcement Technology of Guide Wall of Lattice Diaphragm Wall - CHEN Qiusheng (Renmin Zhujiang)
The geological karst at the upstream intake of Baishiyao shiplock project is developed strongly.When the guide wall of lattice diaphragm wall encounters karst cave in the process of flushing,it is easy to cause uneven settlement and deformation,or even the overall destruction and collapse of the guide wall,which affects the construction quality of diaphragm wall.In order to solve the above difficulties in construction,the steel support members special for guide wall are developed,and successfully applied to the actual project.The example shows that the steel support members can effectively solve the problems of deformation,damage and collapse of guide wall,with the advantages of high support strength,good mobility and reusability,which can provide reference for similar projects.